2013
DOI: 10.1111/jpc.12128
|View full text |Cite
|
Sign up to set email alerts
|

Usage and impact of an online education tool for preventing sudden unexpected death in infancy

Abstract: This simple online education tool achieved its aims of high usage, broad participation and cost-effective impact on increasing confidence to discuss infant sleep safety with others. e-Learning modes should be considered where there is a need to align large numbers of people in a short time with understandings and actions for addressing a specific health issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 3 publications
0
29
0
5
Order By: Relevance
“…Four studies included study samples in which over half of the sample was White [9,12,19,31], and four included samples in which over half of the sample was Black or African American [13,16,21,29]. Eight studies reported diverse samples with less than half of the sample being White or Black, and the remaining sample being other or mixed race/ethnicity [10,15,18,26,28,32,33,38]. Of the studies that reported education level [9,10,12,13,18,19,21,24,26,28,29,31,38], six studies included samples with over half of individuals having a high school diploma/GED or less [9,13,18,21,26,28].…”
Section: Study Location Target Audience and Targeted Behaviorsmentioning
confidence: 96%
See 3 more Smart Citations
“…Four studies included study samples in which over half of the sample was White [9,12,19,31], and four included samples in which over half of the sample was Black or African American [13,16,21,29]. Eight studies reported diverse samples with less than half of the sample being White or Black, and the remaining sample being other or mixed race/ethnicity [10,15,18,26,28,32,33,38]. Of the studies that reported education level [9,10,12,13,18,19,21,24,26,28,29,31,38], six studies included samples with over half of individuals having a high school diploma/GED or less [9,13,18,21,26,28].…”
Section: Study Location Target Audience and Targeted Behaviorsmentioning
confidence: 96%
“…Nineteen studies focused on families and caregivers of newborn infants [9, 10, 12, 13, 15, 16, 18, 21, 24, 26, 28-32, 34-36, 38], eight focused on health care professionals (nurses, midwives, and physicians) [14,17,19,20,23,25,27,37]; the remaining two focused on mainstream health professionals and peers (including some parents) [33], and child care professionals [22]. Of the studies that focused primarily on providers, four also included data on family practices and thus are also included in the summaries for family-focused studies [14,17,19,25].…”
Section: Study Location Target Audience and Targeted Behaviorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a visual support was used, which consisted in a "crib card" placed on cribs and posters with visual information on hallways and waiting rooms. 8 Written material with the information provided in the posters on safe sleep practices was also delivered to participating families, and printed material for one year was left at each site according to the estimated number of births (Figures 1 and 2).…”
Section: Methodsmentioning
confidence: 99%